SOSIALISASI SISTEM INFORMASI INVESTASI PETERNAKAN BERBASIS WEBSITE (E-FARMING) DI CV DIGIS INDONESIA - Ainus Sukma El Diana Putri (Nusantara Journal of Community Engagement, 2020)
E-Farming is a platform that brings together farmers who have ample land for animal husbandry and the ability to raise livestock with capital owners or potential investors who have funds but do not have the ability in terms of raising livestock. This study aims to socialize the website-based livestock investment information system (E-Farming) that can be accessed by all communities both locally and nationally, in which the community can become investors and invest in livestock, investors can choose the slots that exist during the investment period done, then can control the investments that have been followed. The results of this study are to explain how the existing system on the E-Farming website to the public through an approach in the form of socialization.